2003
DOI: 10.1007/978-0-387-35670-9_8
|View full text |Cite
|
Sign up to set email alerts
|

Dimensioning of FDL Buffers for Optical Burst Switching Nodes

Abstract: Optical burst switching (OBS) is a promising candidate for a more dynamic optical layer in the context of IP over WDM. Although buffering is not mandatory for the functionality of OBS, even simple FDL buffers can improve burst loss probability. In this paper, we first discuss principal buffer architectures and reservation schemes for fiber delay line (FDL) buffers. Then, we investigate key design parameters of FDL buffers like FDL delay, buffer architecture and total number of buffer ports. Finally, we introdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 10 publications
2
47
0
Order By: Relevance
“…It has been shown that even FDL buffers with rather simple functionality and low technological requirements can improve OBS performance significantly [8,13,2,14].…”
Section: Principal Contention Resolution Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that even FDL buffers with rather simple functionality and low technological requirements can improve OBS performance significantly [8,13,2,14].…”
Section: Principal Contention Resolution Mechanismsmentioning
confidence: 99%
“…Consequently, all FDLs used for contention resolution have to be shorter than a typical EDFA span of 80 km which limits the maximum FDL delay to 266 µs (c = 2 × 10 8 m/s). Previous work showed that FDL delays should be in the order of a few mean burst durations in order to be efficient [13,8]. In a FDL buffer with 4 FDLs, e.g., a delay of 8 mean burst durations for the longest FDL is a good choice.…”
Section: Principal Contention Resolution Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data channel contention occurs when two or more packets/bursts are simultaneously destined to the same output port on the same wavelength. Standard methods to resolve this issue have been space deflection (deflection routing) [33]- [35], time deflection (buffering) [36], [37], and wavelength conversion [38].However, deflection routing affects the network load and cannot guarantee packet arrival in the correct order, time deflection is impractical due to the lack of scalable optical buffers while wavelength conversion raises the complexity of the node and thus the hardware cost. Moreover, none of the above policies are suitable for the all-optical self-router features of the ARTEMIS switching paradigm.…”
Section: A Contention Protection and Contention-avoidance Mechanismsmentioning
confidence: 99%
“…Many contention resolution schemes for OBS networks have been proposed. These schemes make use of deflection routing [4,16], fiber delay line buffering [5,10], wavelength conversion [6,22], and burst segmentation [15,16].…”
Section: Introductionmentioning
confidence: 99%